From Decoction to Evidence: Modern Standardization of Ayurvedic Kwatha and Polyherbal Formulations (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Standardization of Ayurvedic dosage forms have become a central priority for researchers, industry, and regulators because the clinical credibility of traditional medicines depends on reproducible composition, safety, and performance. Among classical dosage forms, Kwatha Kalpana (aqueous decoctions) represents a foundational extraction technology where heat and water mobilize primarily water-soluble phytochemicals from single or multiple herbs. Despite wide therapeutic use in classical practice, kwathas face practical barriers in contemporary care, labor-intensive preparation, short shelf life, batch-to-batch variability, microbial risk, and poor palatability. This review consolidates the historical rationale, formulation principles, preparation variables, and modernization opportunities for kwatha, while emphasizing polyherbalism as a systems-based strategy that can enhance efficacy through pharmacodynamic complementarity, improved bioavailability, and multi-target action. We synthesize current evidence on analytical standardization (organoleptic/physicochemical indices, microbial/heavy-metal limits, and chromatographic fingerprints) and highlight validated platforms such as HPTLC/HPLC marker quantification—including examples where andrographolide served as a robust marker for a classical decoction standardization workflow. We further outline practical, regulator-aligned pathways, process controls, preservative rationalization, and stability-guided formulation redesign to enable clinically relevant, scalable, and quality-assured kwatha products.